Effect of feeding and management on growth andsurvival of Wallago attu (Scheneider) larvaeduring hatchery rearing - Sahoo, S K; Giri, S S; Sahu, A K; Gupta, S D (Indian Journal of Fisheries, 2014)
Experiments on larval rearing of large freshwater catfish, Wallago attu wereconducted by feeding plankton alone or in combination with minced fish, molluscor goat liver. The performance of larvae fed on different feeds during non-segregation and segregation was analysed with respect to survival. The larvaefed on goat liver along with plankton attained significantly higher (P<0.05)weight, length, specific growth rate, percent weight gain and survival comparedto other groups. The survival of larvae fed on liver with plankton was highest(52%) compared to that of other dietary treatments (26 - 36%). The size gradingdecreased the cannibalism among the larvae. The final weight and length, specificgrowth rate, percent weight gain and survival in liver with plankton fed larvaewere significantly higher (P<0.05) than other treatments. Segregation of larvae during rearing enhanced their rate of survival.